1997
DOI: 10.1111/j.1151-2916.1997.tb03178.x
|View full text |Cite
|
Sign up to set email alerts
|

Sol–Gel Synthesis of Perovskite‐Type Lanthanum Manganite Thin Films and Fine Powders Using Metal Acetylacetonate and Poly(vinyl alcohol)

Abstract: A novel sol-gel process was developed for preparing thin films and fine powders of lanthanum manganite (LaMnO 3 ) with perovskite-type structure. Lanthanum and manganese acetylacetonate powders could be easily dissolved in a mixed solution of methyl alcohol and ethylene glycol (or methyl alcohol and propionic acid) to give a spinnable organic solution as a starting material. Pretreatment of a substrate by poly(vinyl alcohol) (PVA) aqueous solution, a gel former, made it possible to deposit a thin film as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 16 publications
0
32
0
2
Order By: Relevance
“…For this purpose, a complete picture of the thermodynamic stability of LaMnO 3 has been studied extensively by experiment (with X-ray [6][7][8][9][10][11] and neutron diffraction [7,12], scanning [10,11] and transmission electron microscopy [10], electron paramagnetic resonance [9], thermogravimetry (TG) [6,10,12,13], differential thermal analysis (DTA) [11,12], differential scanning [6,8,10] and alternating current calorimetry [8]). However, not much literature can be found that investigates the factors affecting the reactivity of LaMnO 3 as a catalyst in an AFC environment [14].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, a complete picture of the thermodynamic stability of LaMnO 3 has been studied extensively by experiment (with X-ray [6][7][8][9][10][11] and neutron diffraction [7,12], scanning [10,11] and transmission electron microscopy [10], electron paramagnetic resonance [9], thermogravimetry (TG) [6,10,12,13], differential thermal analysis (DTA) [11,12], differential scanning [6,8,10] and alternating current calorimetry [8]). However, not much literature can be found that investigates the factors affecting the reactivity of LaMnO 3 as a catalyst in an AFC environment [14].…”
Section: Introductionmentioning
confidence: 99%
“…4 where XRD patterns for variously annealed LM1000 thin films are shown. It can be seen that all these films exhibit a single-phase perovskitetype LaMnO 3 structure (Shimizu and Murata, 1997). The crystal structure is rhombohedral with space group R-3c.…”
Section: Methodsmentioning
confidence: 83%
“…And it is sometimes difficult to obtain pure phase due to incompletion of the reaction. Soft chemical methods for the synthesis of inorganic solids, such as sol-gel [12,13] or co-precipitation [14], have been studied for a number of years now. But their disadvantages include the high price of raw material, complex operating procedure, etc.…”
Section: Introductionmentioning
confidence: 99%